MOLAB® meets Persia: Non-invasive study of a sixteenth-century illuminated manuscript. (August 2015) - Anselmi, Chiara; Ricciardi, Paola; Buti, David; Romani, Aldo; Moretti, Patrizia; Rose Beers, Kristine; Brunetti, Brunetto Giovanni; Miliani, Costanza; Sgamellotti, Antonio
Abstract : Using the MOLAB ® non-invasive analytical mobile laboratory, we studied a finely illuminated sixteenth-century Persian manuscript at the Fitzwilliam Museum, Cambridge, UK, in collaboration with its Department of Manuscripts and Printed Books. Three miniatures belonging to the manuscript, but ascribable to different periods, were analyzed in order to identify similarities and differences in the painting materials and techniques used by Safavid artists over a period of 150 years. The use of multiple analytical techniques indicated a common palette characterizing the three decorative schemes, along with some differences mainly regarding the pigment mixture used to obtain brown hues in the first scheme, as well as the presence of different mixtures in green and dark purple areas in the third scheme.